Strengthening Self Capacity of ex-Localization of Prostitution Community at Bangunsari Surabaya for Economic Independence through Asset Based Community-Driven Development (ABCD) Approach - Esti Novi Andyarini; Sarita Oktorina; Hamim Rosidi (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2020)
The closure of Bangunsari prostitution localization had a major impact on the economic point of view and lives of the social community in the Bangunsari area and its surroundings. The efforts carried out by Surabaya City Government in providing severance pay and skills training to ex-localization of the prostitution community have not yet restored their economic conditions. The purpose of this community service is to improve the economic independence of the affected community members through strengthening their self capacity. The method used in this community service is the Asset-Based Community-driven Development (ABCD) approach. The results of this Community Service are that the community members: can finally be economically independent by developing assets through the culinary, able to market the product through social media, develop participation in community service programs that have been held, and live a better social life after the closure of prostitution localization at Bangunsari.